THE ROLE OF YOUTH IN ECONOMIC DEVELOPMENT IN THE ERA OF SOCIETY 5.0 - Aries Setiawan (Jurnal Ekonomi dan Bisnis Nias Selatan, 2023)
This article aims to discover the youth's role in economic development in society 5.0. The research method used is literature studies, which collect information and data from written sources such as books, journal articles, and official documents. The results of this literature study show that youth have an important role in economic development in the era of Society 5.0, namely  1) Technology development, namely youth can develop new technologies or improve existing technologies to increase efficiency and productivity in various sectors of the economy; 2) Entrepreneurship, that is,  youth can become innovative entrepreneurs and create new jobs for society; 3) Education, namely youth can be an educator who focuses on providing the skills and knowledge needed in Society 5.0, such as programming, application development, and artificial intelligence; 4)Leadership, namely youth can be a visionary leader and able to create positive change in society and the environment; and 5) Advocacy,  namely youth can be an advocate or activist who fights for the rights and interests of the community in economic development in the era of Society 5.0.